SPECIFIC ASPECTS OF INTELLECTUAL DEVELOPMENT IN STUDENTS OF DIFFERENT AGES - O. I. Yadgarova; D. A. Hotamova (Web of Journals Publishing, 2023)
In this article, students of different age groups because of the fact that they are creatively and socially diverse, recommendations for increasing their level of mastery are given. Also, the role of education in the development of a person as a person is incomparable, without knowing the psychological characteristics of children of a certain age, it is impossible to provide them with appropriate education and upbringing and how to increase the effectiveness of the lesson in the process of conducting lessons thoughtful thoughts about.
Keywords: age periods, learning, education, educational personality, development, lesson effectiveness.